2018
DOI: 10.1182/blood-2017-07-798728
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of heme oxygenase ameliorates anemia and reduces iron overload in a β-thalassemia mouse model

Abstract: Thalassemias are a heterogeneous group of red blood cell disorders, considered a major cause of morbidity and mortality among genetic diseases. However, there is still no universally available cure for thalassemias. The underlying basis of thalassemia pathology is the premature apoptotic destruction of erythroblasts causing ineffective erythropoiesis. In β-thalassemia, β-globin synthesis is reduced causing α-globin accumulation. Unpaired globin chains, with heme attached to them, accumulate in thalassemic eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 63 publications
3
23
1
Order By: Relevance
“…As shown in Figure S3 in the Supporting Information, a higher level in L1‐2 and L1‐3 and a lower level in L4‐3 for the tissue MDA were found, respectively, in agreement with their differential tissue iron content. In support of this finding, discrepant induction of crucial regulators against oxidative stress, including nuclear factor (erythroid‐derived2)‐like2 (Nrf2)37 and heme oxygenase‐1 (HO‐1),38 was demonstrated in these zones (Figure 1F and Figure S2D,E, Supporting Information), consistent with their corresponding iron levels.…”
supporting
confidence: 59%
“…As shown in Figure S3 in the Supporting Information, a higher level in L1‐2 and L1‐3 and a lower level in L4‐3 for the tissue MDA were found, respectively, in agreement with their differential tissue iron content. In support of this finding, discrepant induction of crucial regulators against oxidative stress, including nuclear factor (erythroid‐derived2)‐like2 (Nrf2)37 and heme oxygenase‐1 (HO‐1),38 was demonstrated in these zones (Figure 1F and Figure S2D,E, Supporting Information), consistent with their corresponding iron levels.…”
supporting
confidence: 59%
“…Upon maturation, RBCs from WT mice progressively eliminated their mitochondria, with only 1.5% of terminally differentiated RBCs retaining RBCs for phagocytosis by scavenging macrophages that deliver the damaged RBCs to spleen and liver for degradation (33). The released heme is catabolized by heme oxygenase 1 (HMOX1), which is upregulated in β-thalassemia due to excessive RBC apoptosis (34). VIT-2763 treatment significantly reduced the expression of Hmox1 in livers of Hbb th3/+ mice, most likely as a result of the decreased RBC turnover ( Figure 10B).…”
Section: Resultsmentioning
confidence: 99%
“…Heme plays a key role in normal erythropoiesis and in the alterations observed in β-thal erythropoiesis (3,5,17). We and others have shown biphasic behavior in heme biosynthesis, characterized by heme accumulation in the early phase of β-thal erythropoiesis, followed by a relative heme reduction in the late phase of β-thal erythropoiesis (3).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that modulation of heme homeostasis might affect erythropoiesis (16) and beneficially affect β-thal erythroid maturation (17). In erythroblasts, glycine uptake via the glycine carrier system, GlyT1, is a key determinant of the rate of heme biosynthesis and bioavailability (18,19).…”
Section: Introductionmentioning
confidence: 99%